Deification of Women‟s Roleat Household Level SansEmancipation: Insights from Odisha, India - Bose, Meenakshi; Panda, Smita Mishra (International Journal of Psychosocial Rehabilitation, 2020)
Inrecorded Indian history, women‟s status has been subjected to many changes. There are several factors that validate the privileged position enjoyed by women in ancient India.Socio-cultural constructswith religious overtones, of assigning roles to gender have a significant impact on defining women‟s role within the society. The conditioning of women based on the religio-cultural expectations lead to their subjugated position in the society.This paper attempts to understand the role of women within the household with the help ofreal-life analysis of casestudies collected in Khordha district in Odisha. This illustrates the different roles of women aligned with their cultural interpretation through history embedded in religious scriptures. It simultaneously discusseshow the position of women has declined in due course of time in history, underscoring the contradictions as well. The article brings out that deification of women at the household level does not lead to their emancipation and empowerment.